2000
DOI: 10.25249/0375-7536.2000303481485
|View full text |Cite
|
Sign up to set email alerts
|

The Triassic Taphoflora From Parana Basin, Southern Brazil: An Overview

Abstract: A Triassic Dicroidium Flora identified in the central region of the State of Rio Grande do Sul, Southern Brazil, represents an important biostratigraphic stage in the palaeofloristic succession of Parana basin. The megafloristic association composed of compressed leaves, fronds and seeds shows a predominance of the genus Dicroidium, with several species, and other important taxa like Neocalamites sp, Cladophlebis sp., Tetraptilon aff. heteromerum, Ginkgoites antarctica, Sphenobaiera sp, Podozamites sp, Nilsson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The oldest examples, from the Lower Permian Itararé Group and Rio Bonito Formation, include incomplete leaves of Ginkgoites eximia Seward, Ginkgophytopsis Høeg, Dicranophyllum and Cheirophyllum speculare Césari and Cúneo, the latter exhibiting dubious affinities to the Ginkgoales (Silva and Iannuzzi, 2000). They were associated with assemblages composed mostly by pteridosperms (Glossopteris and Gangamopteris), accompanied by sphenopsids and primitive conifers (Guerra-Sommer et al, 1999;Guerra-Sommer and Klepzig, 2000).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The oldest examples, from the Lower Permian Itararé Group and Rio Bonito Formation, include incomplete leaves of Ginkgoites eximia Seward, Ginkgophytopsis Høeg, Dicranophyllum and Cheirophyllum speculare Césari and Cúneo, the latter exhibiting dubious affinities to the Ginkgoales (Silva and Iannuzzi, 2000). They were associated with assemblages composed mostly by pteridosperms (Glossopteris and Gangamopteris), accompanied by sphenopsids and primitive conifers (Guerra-Sommer et al, 1999;Guerra-Sommer and Klepzig, 2000).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The genus becomes a common element of fossil assemblages in Spathian strata (RETALLACK 1977;HOLMES & ASH 1979) and dominates floras in succeeding strata up to theend-Triassic extinction horizon (BALME et al 1995). Dicroidium has its centre of distribution in the middle and high palaeolatitudes of Gondwana, with particularly large collections described from the Middle to Upper Triassic of South Africa (DU TOIT 1927;THOMAS 1933;ANDERSON & ANDERSON 1983), South America (FRENGUELLI 1943(FRENGUELLI , 1944bBORTOLUZZI & BARBERENA 1967;ARCHANGELSKY 1968;PETRIELLA 1981;GUERRA-SOMMER & CAZZULO KLEPZIG 2000), Antarctica (TOWNROW 1967;BOUCHER et al 1993;BOMFLEUR & KERP 2010;ESCAPA et al 2011;BOMFLEUR et al 2012), India (e.g., FEISTMANTEL 1879aPAL et al 2014;RAO & LELE 1962;SEWARD 1932), Australia (e.g., WALKOM 1917, 1925a, 1928JONES & DE JERSEY 1947;TOWNROW 1957;HOLMES & ANDERSON 2005;PATTEMORE 2016), and New Zealand (e.g., ARBER 1913RETALLACK 1980b).…”
Section: [Full Column Table 1]mentioning
confidence: 99%
“…Horn et al (2018b) identified some climatic changes between the SMS biozones, from driest to wetter, in particular between the lowermost (Dinodontosaurus and Santacruzodon) and the uppermost (Hyperodapedon and Riograndia). Guerra-Sommer and Klepzig (2000) and Barboni and Dutra (2015) reported occurrences of leaves, Cuticule fragments and ex situ fossil woods, with a predominance of the genus Dicroidium, in the Middle-Upper Triassic package (Passo das Tropas Member) paleoflora. This genus includes the Division Ginkgophyta.…”
Section: Elements(%)mentioning
confidence: 99%